2022
DOI: 10.3390/ijerph192013071
|View full text |Cite
|
Sign up to set email alerts
|

eHealth: A Survey of Architectures, Developments in mHealth, Security Concerns and Solutions

Abstract: The ramifications of the COVID-19 pandemic have contributed in part to a recent upsurge in the study and development of eHealth systems. Although it is almost impossible to cover all aspects of eHealth in a single discussion, three critical areas have gained traction. These include the need for acceptable eHealth architectures, the development of mobile health (mHealth) technologies, and the need to address eHealth system security concerns. Existing survey articles lack a synthesis of the most recent advanceme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 192 publications
0
5
0
Order By: Relevance
“…While eHealth informatics offers significant benefits, it also brings its own set of challenges, such as data security concerns, interoperability issues, and the need for proper training and integration within healthcare systems [15] .…”
Section: Literature Reviewmentioning
confidence: 99%
“…While eHealth informatics offers significant benefits, it also brings its own set of challenges, such as data security concerns, interoperability issues, and the need for proper training and integration within healthcare systems [15] .…”
Section: Literature Reviewmentioning
confidence: 99%
“…These allowed a better quality when applying the use of federated learning in order to improve medical care [98]. Another systematic review [99] on mHealth applications used for identification and treatment of medical care used in eHealth used Scopus, ACM Digital Library, IEEE Xplore, Springer Link, PubMed, and Scopus databases [99]. A total of 250 articles relevant to the systematization of the literature were identified and it was concluded that there can be no single method to ensure the safety of all eHealth systems [99].…”
Section: Related Articlesmentioning
confidence: 99%
“…The COVID-19 pandemic has contributed to the increase in the research and development of e-health systems. Although there are many aspects, three areas can be singled out as key areas: the architecture of e-health, the development of mobile healthcare technologies, and the field of security of e-health systems (Alenoghena et al, 2022). E-health includes health informatics, electronic health record, electronic entry of medical orders, electronic prescriptions, telemedicine, and mobile healthcare.…”
Section: E-healthmentioning
confidence: 99%